English Pre-Service Teachers’ Ability to Use Artificial Intelligence-Based Application in Reading Comprehension - Yudhiantara, Rully Agung; Hamdan Sugilar (Loquen, 2023)
This research article delves into the exploration of English pre-service teachers' proficiency in utilizing an artificial intelligence-based application, specifically Quillbot, to enhance reading comprehension within the context of English for Islamic studies. Qualitative data are derived from questionnaire, learning tasks and focus group discussions, which delve into students' perspectives on artificial intelligence for language learning and language teaching.The results indicate that English pre-service teachers adeptly harnessed Quillbot to paraphrase text from articles, effectively enhancing reading comprehension. Beyond paraphrasing, students demonstrated their analytical skills by subjecting Quillbot's output to grammar analysis. Moreover, the study showcased participants' comprehension abilities as they crafted questions and answers rooted in the article's content. Ultimately, the findings underscore the participants' favorable outlook on AI tools for facilitating language learning and teaching, accentuating the positive stance of English pre-service teachers toward integrating AI technologies into language education.